Immunoregulatory silicon-deposited implant promotes osseointegration. (15th April 2023) - Wang, Tao; Chen, Xu; Zhang, Yin; Ye, Tingjun; Liu, Zhihong; Wang, Lei; Cui, Wenguo; Pan, Guoqing; Zuo, Guilai; Deng, Lianfu
Abstract: Silicon-based implants have proven capable of promoting osteogenesis and significantly improving osseointegration at bone-to-implant interfaces. However, the early immunomodulatory role of silicon and the possible mechanisms by which osteogenesis is enhanced have not yet been established. In the present study, a silicon-releasing coating for titanium substrates was fabricated using electron beam evaporation (EBE)-assisted silicon deposition. Immunological analysis demonstrated that the silicon coating activated an anti-inflammatory macrophage phenotype (M2) through the production of anti-inflammatory cytokines ( e.g., IL10) and pro-osteogenic factors ( e.g., BMP2), creating an osteoimmune microenvironment conducive to interfacial osteogenesis. Bioinformatics analysis indicated that the released silicon up-regulated 65 microRNA (miRNA) and down-regulated 73 miRNA molecules. The target genes of these miRNA molecules were principally involved in inflammatory-related pathways, including down-regulation of M1-related signaling pathways ( e.g., PI3K-Akt, mTOR, and HIF-1) and up-regulation of M2-related signaling pathways ( e.g., Rap1, MAPK, and TNF). Thus, we demonstrate here the immunomodulatory and osteoinductive role of a silicon-deposited coating on Ti-based osteoimplants. The mechanism of silicon-enhanced osteoimmunology established in the present study using silicon deposition technology provides both the practical means and theoretical evidence to improve implant-to-bone osseointegration.